Decarbonised Future Regional Airport Infrastructure - Markus Meindl; Cor de Ruiter; Valerio Marciello; Mario Di Stasio; Florian Hilpert; Manuela Ruocco; Fabrizio Nicolosi; Nils Thonemann; Karen Saavedra-Rubio; Louis Locqueville; Alexis Laurent; Martin Maerz (Aerospace, 2023)
Sustainability and, especially, emission reductions are significant challenges for airports currently being addressed. The Clean Sky 2 project GENESIS addresses the environmental sustainability of hybrid-electric 50-passenger aircraft systems in a life cycle perspective to support the development of a technology roadmap for the transition to sustainable and competitive electric aircraft systems. This article originates from the GENESIS research and describes various options for ground power supply at a regional airport. Potential solutions for airport infrastructure with a short (2030), medium (2040) and long (2050) time horizon are proposed. This analysis includes estimating the future energy demand per day, month and year. In addition, the current flight plan based on conventional aircraft is adapted to the needs of a 50-PAX regional aircraft. Thus, this article provides an overview of the energy demand of a regional airport, divided into individual time horizons.